Symbolic Significance of Contemporary Nepali Sculptures - Sharma, Yam Prasad (Journal of Fine Arts Campus, 2023)
Contemporary Nepali sculptures suggest ideas, concepts, and invisible reality through symbols. The symbols are images that suggest ideas beyond themselves. The symbols link the visible world to the invisible reality indicated by the artworks. The symbolic sculptures suggest spiritual, social, and political ideas indirectly from the distance. Such symbolic arts can be interpreted in multiple ways since the signifier and the signified are not directly linked. The symbols in these sculptures bring the narratives of creation, cooperation, harmony, and human existence. The fish is the symbol of nonviolence. Lotus is the symbol of enlightenment. Some symbols are established by the cultural tradition, whereas some symbols are uniquely created by the artists themselves. Contemporary Nepali sculpture is an area of research which has been studied from the perspective of symbolism. This is qualitative research since the sculptures can be interpreted in multiple ways.